ROZSTRZYGANIE SPORÓW POMIĘDZY JEDNOSTKĄ I ADMINISTRACJA˛ W SYSTEMACH COMMON LAW (REFLEKSJE NA KANWIE KSIĄŻKI SARY BLAKE ADMINISTRATIVE LAW IN CANADA) - Kmieciak, Zbigniew (Wydział Prawa i Administracji UAM, 2012)
The paper presents issues that are the main subject of Sara Blake’s ‘Administrative Law in Canada.’ Sara Blake has practiced general civil litigation since 1997. She is a lawyer with the Ontario Ministry of the Attorney General, Crown Law Office – Civil Law, where she acts for the government ministries and agencies in appeals, civil actions, applications for judicial review and tribunal hearings. In her opinion: ‘Administrative law is the law that governs how these decisions are made in individual cases’ (p. 4). Therefore, her book concerns the proceedings before administrative tribunals and a review of their actions. The book is divided into two parts. The first part (chapters 2 to 5) describes the rules according to which tribunals are expected to operate. The generic term ‘tribunal’ is used to include all public officials, boards and agencies who exercise statutory authority. The second part (chapters 6 to 9) explains the types of redress that are available and how they may be obtained. Tribunals belong to the administrative, not the judicial, arm of government, even though at times they may appear to be remarkably court-like. The specific kind of tribunals (the appellate tribunals) may, and do, engage in review of the merits of a decision and usually have the powers to vary, or substitute with another, the decision of the original decision-maker. Except to the extent authorised by statute, members of adjudicative tribunals should be independent of those who appoint them and pay their salaries. Only in that way can they adjudicate each case free from interference. However, as Sara Blake underlines, ‘There is no constitutional right to a hearing before independent and impartial tribunal’. In her view, the test for independence of judges, which has a constitutional basis, cannot apply to tribunals, ‘which are creatures of statute and operate as part of government’. Administrative tribunals cannot be as independent as judges because ‘tribunals are established to implement and, often, to make government policy’ (p. 107). The requirement for independence was developed in the adjudicative context of the courts. It cannot be strictly applied to a policy-making context, said Sara Blake. The author of this paper is of the opinion that the idea of external review by independent but non-judicial bodies opens promising perspectives for the development of administrative law also in Poland.
SETTLING OF DISPUTES BETWEEN AN INDIVIDUAL AND AN ADMINISTRATIVE ORGAN IN THE COMMON LAW SYSTEM (REMARKS ON THE ‘ADMINISTRATIVE LAW IN CANADA’ BY SARA BLAKE)
Keywords: Trybunał Administracyjny; rzetelny proces; sądowa kontrola administracyjna; administrative tribunal; fair trial; judicial review of administration